Vitamin D decreases STAT phosphorylation and inflammatory cytokine output in T-LGL leukemia. Issue 5 (4th May 2017) - Olson, Kristine C.; Kulling, Paige M.; Olson, Thomas L.; Tan, Su-Fern; Rainbow, Rebecca J.; Feith, David J.; Loughran, Thomas P.
ABSTRACT: Large granular lymphocyte leukemia (LGLL) is a rare incurable chronic disease typically characterized by clonal expansion of CD3+ cytotoxic T-cells. Two signal transducer and activator of transcription factors, STAT1 and STAT3, are constitutively active in T-LGLL. Disruption of this activation induces apoptosis in T-LGLL cells. Therefore, considerable efforts are focused on developing treatments that inhibit STAT activation. Calcitriol, the active form of vitamin D, has been shown to decrease STAT1 and STAT3 phosphorylation in cancer cell lines and autoimmune disease mouse models. Thus, we investigated whether calcitriol could be a valid therapeutic for T-LGLL. Calcitriol treatment of the TL-1 cell line (model of T-LGLL) led to decreased phospho-Y701 STAT1 and phospho-Y705 STAT3 and increased vitamin D receptor (VDR) levels. Doses of 10 and 100 nM calcitriol also significantly decreased the inflammatory cytokine IFN-γ in the TL-1 cell line. The overall cell viability did not change when the TL-1 cell line was treated with 0.1 to 1000 nM calcitriol. Studies with primary T-LGLL patient peripheral blood mononuclear cells showed that the majority of T-LGLL patients have detectable VDR and activated STATs in contrast to normal donor controls. Treatment of primary T-LGLL patient cells with calcitriol recapitulated findings from the TL-1 cell line. Overall, our results suggest that calcitriol may reprogram T-cells to decrease essential STAT activation and pro-inflammatory cytokine output. These data support further investigation into calcitriol as an experimental therapeutic for T-LGLL.